2019
DOI: 10.1177/1077800419879186
|View full text |Cite
|
Sign up to set email alerts
|

Explorations Across National Borders: Wor(l)ding Differences Together

Abstract: In this article, we explore expansions of our perspectives on pedagogical phenomena in Early Childhood Education through textual- and meta-textual encounters and open-ended dataphilosophy. This implies experimenting with our epistemic understandings of pedagogies and pedagogical research and the ontological models that we have brought to bear. The texts revolve around working doubts, development of pedagogical thoughts and research, and formation of mental images, worldviews, and values. Researchers from Russi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…It should be noted that the current situation is characterized by a significant increase in the risks of inclusive education, including the insufficient sensitivity of teachers to the individual demonstrations of a particular student, the dynamics of their educational needs, which does not allow fully revealing the educational potential of each child (Chernik et al, 2019). Our analysis of a large amount of information showed that in the current practice of inclusive education in the field of individualizing the activities of students with health limitations, such components as professional flexibility, compromise, creativity, communication, empathy are not adequately reflected.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the current situation is characterized by a significant increase in the risks of inclusive education, including the insufficient sensitivity of teachers to the individual demonstrations of a particular student, the dynamics of their educational needs, which does not allow fully revealing the educational potential of each child (Chernik et al, 2019). Our analysis of a large amount of information showed that in the current practice of inclusive education in the field of individualizing the activities of students with health limitations, such components as professional flexibility, compromise, creativity, communication, empathy are not adequately reflected.…”
Section: Introductionmentioning
confidence: 99%